NIS expression in thyroid tumors, relation with prognosis clinicopathological and molecular features. Issue 1 (January 2018) - Tavares, Catarina; Coelho, Maria João; Eloy, Catarina; Melo, Miguel; da Rocha, Adriana Gaspar; Pestana, Ana; Batista, Rui; Ferreira, Luciana Bueno; Rios, Elisabete; Selmi-Ruby, Samia; Cavadas, Bruno; Pereira, Luísa; et al.
Abstract : Thyroid cancer therapy is based on surgery followed by radioiodine treatment. The incorporation of radioiodine by cancer cells is mediated by sodium iodide symporter (NIS) (codified by the SLC5A5 gene), that is functional only when targeted to the cell membrane. We aimed to evaluate if NIS expression in thyroid primary tumors would be helpful in predicting tumor behavior, response to therapy and prognosis. NIS expression was addressed by qPCR and immunohistochemistry. In order to validate our data, we also studied SLC5A5 expression on 378 primary papillary thyroid carcinomas from The Cancer Genome Atlas (TCGA) database. In our series, SLC5A5 expression was lower in carcinomas with vascular invasion and with extrathyroidal extension and in those harboring BRAF V600E mutation. Analysis of SLC5A5 expression from TCGA database confirmed our results. Furthermore, it showed that larger tumors, with locoregional recurrences and/or distant metastases or harboring RAS, BRAF and/or TERT promoter ( TERT p) mutations presented significantly less SLC5A5 expression. Regarding immunohistochemistry, 12/211 of the cases demonstrated NIS in the membrane of tumor cells, those cases showed variable outcomes concerning therapy success, prognosis and all but one were wild type for BRAF, NRAS and TERT p mutations. SLC5A5 mRNA lower expression is associated with features of aggressiveness and with key genetic alterations involving BRAF, RAS and TERT p. Mutations in these genes seem to decrease protein expression and its targeting to the cell membrane. SLC5A5 mRNA expression is more informative than NIS immunohistochemical expression regarding tumor aggressiveness and prognostic features.